Effect of Toll-like receptor activation on Chikungunya virus replication, proinflammatory cytokine production, Type I interferons and interferon-stimulated genes expression in monocytes and MDM in-vitro infected (2020)
ABSTRACT: Introduction: The chikungunya virus (CHIKV) is an emerging virus that has generated major problems in public health, due to the epidemic’s outbreaks in tropical y subtropical regions. The CHIKV is transmitted by the bite of infected Aedes mosquitoes, and is known to target different human cells types, such as primary monocytes and macrophages. The CHIKV recognition by pattern recognition receptors, including toll-like receptors, expressed by monocytes and macrophages leads in the inflammatory response, including type I interferon (IFN-I), which is involved in innate immune response. The IFN-I induced the expression of IFN-stimulated genes that protect the cells against viral infection. However, monocytes and macrophages have been linked to severe symptoms, due to the high production of IL-6 and TNF-α, two proinflammatory cytokines. Herein, this study aimed to evaluate if Toll-like receptors activation influence CHIKV replication, proinflammatory cytokine production, IFN-I and IFN-stimulated genes expression in monocytes and monocyte-derived macrophages (MDM) in vitro infected with CHIKV. Methodology: Monocytes and MDM were infected with CHIKV and co-stimulated with TLRs agonists. The viral titers were performed by plaque assay method in the cells culture supernatants. Furthermore, the culture supernatants were used to quantify the pro-inflammatory cytokines by ELISA and the level mRNA of ISGs were performed by RT-PCR. Results: We found that both monocytes and MDM are target cells of CHIKV infection, with a maximum peak at 24 h.p.i. and then the production of infectious viral particles drops dramatically. Furthermore, although the activation of TLR-2/6, -3 and -4 do not have a significant effect in CHIKV replication, the activation of TLR-7/8 with R848 agonist significantly decreased the production of infectious viral particles from 6 h.p.i until 48 h.p.i. Likewise, we found a statistically significant increase in the production of IL-6 and TNF-α at 48 h.p.i. Besides, a slight increase in the IFN-beta mRNA level was observed in monocytes at 6 h.p.i., in response to TLR-7/8 activation, as well as a slight increase in the level of the PKR mRNA at 24 h.p.i. and a significant increase in OAS2 at 6, 24 and 48 h.p.i. but it is statistically significant, only at 48 h.p.i. However, in MDMs the activation of TLRs did not regulate viral replication, although a tendency in decrease TNF-alpha was observed at 6 and 24 hpi with the activation of TLR-4 and a tendency to increase IL-6 and TNF-alpha in response to activation of the TLR-7/8.These results suggests a difference in the activation of the two cell populations to CHIKV infection and shed light on the importance of monocytes and macrophages in the pathogenesis and/or resolution of CHIK fever. Conclusion: The results suggest that monocytes and MDMs are targets of CHIKV infection with a maximum peak at 24 h.p.i. but both inflammatory and antiviral responses are different in the two cell populations.